2017
DOI: 10.1002/jsfa.8649
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of quality and safety of Atlantic cod (Gadus morhua) fillets during cold storage, as affected by different thawing methods of pre‐rigor frozen headed and gutted fish

Abstract: BACKGROUNDThe catch of marine whitefish is typically seasonal, whereas the land‐based processing industry has a need for all‐year stable supply of raw materials. This challenge can be met by applying fish frozen at sea. When using frozen fish, the methods employed for thawing may influence the safety and quality of the final product. This study aimed to investigate the applicability of novel thawing strategies in order to provide an all‐year supply of high‐quality and safe cod products.RESULTSComparative inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Meanwhile, the cooking loss is related to the protein denaturation during cooking process (Roiha et al., 2018). In addition, Lorenzo and Domínguez (2014) also express that cooking loss may be due to heat-induced protein denaturation during cooking, which leads to loss of water in the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the cooking loss is related to the protein denaturation during cooking process (Roiha et al., 2018). In addition, Lorenzo and Domínguez (2014) also express that cooking loss may be due to heat-induced protein denaturation during cooking, which leads to loss of water in the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…The observed drip losses (Table 2) was markedly lower than previously observed with cod from other regions and production methods. Frozen-at-sea cod from the Norwegian Sea had a drip loss in the range of 1.7 -3.3 % for refreshed fillets in air (Roiha, Jónsson, Backi, Lunestad, & Karlsdóttir 2017;Roiha et al 2018). Whiting had drip losses of, respectively, 6.0 -9.0 % and 9.4 -16.4 % for refreshed fish in air and MAP (Fagan, Gormley & Uí Mhuircheartaigh, 2003;Fagan, Gormley & Uí Mhuircheartaigh, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Frozen storage for less than one months extended shelf-life of chilled refreshed cod marginally whereas sensory shelf-life was extended 3-4 days in ice following frozen storage periods up to twelve months (Magnússon & Martinsdóttir, 1995;Vyncke, 1983). After frozen storage during one to 12 months at -20 °C to -28 °C, several studies with cod from Belgium, Iceland and Norway found sensory shelf-life of 7 -15 days in ice for refreshed cod in air (Hansen et al, 2015;Martinsdottir & Magnusson, 2001;Roiha et al, 2017;Vyncke, 1983). Fresh cod from CBA in Greenland had sensory shelf-life of 15 days in air (Sørensen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With the growth of market demand and the achievement of good taste, the quality of bigeye tuna has been paid more attention. Among varieties of preservation techniques, cold storage (−1–8 °C) is the most convenient storage method currently used to delay fresh fish spoilage and prolong its shelf life [2]. According to its high nutritional value and delicious meat, tuna has been investigated for quality changes, including chemical composition, microbial growth, enzymatic activities and physicochemical properties, during cold storage [3].…”
Section: Introductionmentioning
confidence: 99%